Use of ICT for administrative tasks by distance learning students of university of Ibadan, Nigeria (2010)
A study of 175 Distance Learning students from the Faculty of Education, University of Ibadan to determine their ICT use for admission and registration was investigated. Data was collected using a questionnaire and interview. Findings revealed that ICT was used for the purchase and filling of admission forms while the registration process involved filling of biodata and courses. Majority of the students used the cyber-cafe as access points for their admission (64.6 %>) and 72.8% for registration process. Over 68.4% of the respondents used ICT for admission, while over 95%> used it for their registration processing. The major constraints to ICT use for these tasks were: cumbersome procedure, unreliability of Internet service providers (ISPs), unstable power supply and high cost of accessing the Internet. Training should be given to the students to enhance their ICT skills and the internet connectivity should be more stable for easy access to perform the tasks.